Identifying key drivers of food price inflation in Malaysia - Norazman, Umi Zakiah; Khalid, Haniza; Mat Ghani, Gairuzazmi (2016)
In Malaysia, food price inflation reached its highest level at 8.8% in mid-2008 compared to overall inflation of 5.5% for the same period, mainly blamed on the spike in world commodity prices. However, recent moves by the government to rationalize food and energy subsidies have also led to higher than normal headline inflation figures and cause public concern. This study examines the pattern of retail food price changes and also explores the link between world raw food prices and subsidies on domestic retail prices. A vector error correction model (VECM) of monthly data (1991-2013) confirms that real effective exchange rate and world oil price primarily determine the food price in Malaysia. World food commodity prices matter as well but this effect is primarily indirect via the impact with labor cost on world agriculture prices, the latter’s change being subsequently passed through on the domestic retail prices. Given the expectation of unstable macro conditions in global market, world commodity price is likely to be uncertain in the future, understanding the dynamics of these shocks on domestic retail price is important for future macroeconomics policy design.